Evidence-based interventions to treat chronic low back pain: treatment selection for a personalized medicine approach. (30th September 2022) - Mauck, Matthew C.; Aylward, Aileen F.; Barton, Chloe E.; Birckhead, Brandon; Carey, Timothy; Dalton, Diane M.; Fields, Aaron J.; Fritz, Julie; Hassett, Afton L.; Hoffmeyer, Anna; Jones, Sara B.; McLean, Samuel A.; et al.
Abstract : Literature on current treatments for chronic low back pain (cLBP) were reviewed and 4 interventions were recommended for inclusion in a multisite cLBP clinical trial. Abstract: Introduction: Chronic low back pain (cLBP) is highly prevalent in the United States and globally, resulting in functional impairment and lowered quality of life. While many treatments are available for cLBP, clinicians have little information about which specific treatment(s) will work best for individual patients or subgroups of patients. The Back Pain Research Consortium, part of the National Institutes of Health Helping to End Addiction Long-term SM (HEAL) Initiative, will conduct a collaborative clinical trial, which seeks to develop a personalized medicine algorithm to optimize patient and provider treatment selection for patients with cLBP. Objective: The primary objective of this article is to provide an update on evidence-based cLBP interventions and describe the process of reviewing and selecting interventions for inclusion in the clinical trial. Methods: A working group of cLBP experts reviewed and selected interventions for inclusion in the clinical trial. The primary evaluation measures were strength of evidence and magnitude of treatment effect. When available in the literature, duration of effect, onset time, carryover effect, multimodal efficacy, responder subgroups, and evidence for the mechanism of treatment effect or biomarkers were considered. Conclusion: The working group selected 4 leading, evidence-based treatments for cLBP to be tested in the clinical trial and for use in routine clinical treatment. These treatments include (1) duloxetine, (2) acceptance and commitment therapy, (3) a classification-based exercise and manual therapy intervention, and (4) a self-management approach. These interventions each had a moderate to high level of evidence to support a therapeutic effect and were from different therapeutic classes.